Pengaruh PENGARUH CITRA MEREK TERHADAP LOYALITAS KONSUMEN PADA RESTORAN ME GACOAN DI PANJER, DENPASAR, BALI - Sudiparwati, Putu Ayu; Arcana, I Nyoman; Massenga, Lidjah Magdalena (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Competition in the culinary industry makes restaurant managers try to find the right strategy to be competitive. One strategy is to increase buying interest and loyalty. This research was conducted on consumers of Me Gacoan restaurant in the Panjer area, Denpasar. The purpose of this study was to determine the magnitude of the influence of brand image on consumer loyalty. Brand Image indicators in this study consist of: Recognition, Reputation, Affinity, and Buying Interest. While consumer loyalty indicators consist of: consumer liking for the product and consumer loyalty to the brand. Data collection used questionnaire distribution to 64 respondents. The results of simple linear regression analysis show that Brand Image variables have a significant effect on Loyalty. There is a positive influence of brand image on consumer loyalty, which means that Brand Image in Me Gacoan restaurants has a positive and significant effect on consumer loyalty. This study recommends that Me Gacoan maintain product quality, price, and services to customers so that customers do not switch to other brands that sell products, services, and prices that are almost the same around the city of Denpasar.